Reducing the Tendency to Aggress: Insights from Social and Personality Psychology. Issue 6 (18th June 2013) - Meier, Brian P.; Wilkowski, Benjamin M.
Abstract: The social and personality psychology literature on aggression has largely focused on the factors that are associated with an increase in aggression such as provocation, violent media exposure, and trait anger. This work has been quite important in developing models of aggression. Less emphasis, however, has been placed on examining the factors that reduce this harmful behavior. We use a widely researched model of aggression to examine some factors that are associated with aggression reduction including self‐control, pro‐social experiences, and appraisal processes. These variables reduce the tendency to aggress, and our review addresses some potential processes involved. We suggest that a stronger research focus on the factors that reduce aggression can aid our understanding of not only why aggression occurs but also how to control it.